Social skills of the schoolchildren attending physical educations lessons - Navitskaite S., Sniras S. A. (Pedagogy and psychology: development prospects, 2019)
in recent years researchers are paying more and more attention to the social skills of schoolchildren but we still lack research works on the social skills of the schoolchildren attending PE classes. the authors outlines that for this reason, the level of the social skills in the PE lessons and the importance of social skills for the schoolchildren will be discussed in the article.
Keywords: дети дошкольного возраста; коммуникативные навыки; social skills; возникающие в определенной ситуации; social situational skills; shoolchildren